The Leadership Experience, 7th Edition - Richard Daft (Cengage Learning, 2017)
Master the critical leadership skills and solid understanding of theory needed to become an effective business leader in today's turbulent times with THE LEADERSHIP EXPERIENCE, 7E. Acclaimed author Richard Daft helps you explore the latest thinking in leadership theory and contemporary practices at work within organizations throughout the world. You'll examine emerging topics, including enhancement of emotional intelligence, leadership vision and courage, and leadership of virtual teams, and you'll connect those topics to recent world events such as ethical scandals, leader successes and mistakes, and political turmoil. Packed with memorable examples and unique insights into actual leadership decisions, this full-color text includes crisp, clear visuals to reinforce the book's engaging presentation. This edition's proven applications, specifically designed for today's leadership theory and applications course, and a solid foundation grounded in established scholarly research make the topic of leadership come alive.